2002
DOI: 10.1038/sj.onc.1205132
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HOS expression and activities by Wnt pathway

Abstract: bTrCP and HOS are closely related F-box proteins, which play key roles in ubiquitination and degradation of b-catenin and IkB through associating with those phosphorylated substrates and recruiting SCF E3 ubiquitin ligase. Here we report that activation of Wnt/b-catenin signal transduction pathway elevates bTrCP levels but inhibits expression of HOS in 293T cells. Similar disparity is likely to exist in human colorectal tumors. In the NIH3T3 cells, which express HOS, but not bTrCP, Wnt/b-catenin signaling lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…The redundancy may explain to the mild testicular phenotype observed in the in vivo ablation of b-TrCP1 (Spiegelman et al 2000;Ballarino et al 2004). b-TrCP1 mRNA stability is also increased following Jun amino-terminal kinase (Jnk) activation in a transcription-independent manner (Spiegelman et al 2002). The transcriptional regulation of b-TrCP2, however, is probably different, with Wnt stimulus leading to its transcriptional inhibition and mitogen-activated signaling resulting in a b-TrCP2 transcriptional increase (Spiegelman et al 2002).…”
Section: The Ikb E3 Ubiquitin Ligasementioning
confidence: 99%
See 1 more Smart Citation
“…The redundancy may explain to the mild testicular phenotype observed in the in vivo ablation of b-TrCP1 (Spiegelman et al 2000;Ballarino et al 2004). b-TrCP1 mRNA stability is also increased following Jun amino-terminal kinase (Jnk) activation in a transcription-independent manner (Spiegelman et al 2002). The transcriptional regulation of b-TrCP2, however, is probably different, with Wnt stimulus leading to its transcriptional inhibition and mitogen-activated signaling resulting in a b-TrCP2 transcriptional increase (Spiegelman et al 2002).…”
Section: The Ikb E3 Ubiquitin Ligasementioning
confidence: 99%
“…b-TrCP1 mRNA stability is also increased following Jun amino-terminal kinase (Jnk) activation in a transcription-independent manner (Spiegelman et al 2002). The transcriptional regulation of b-TrCP2, however, is probably different, with Wnt stimulus leading to its transcriptional inhibition and mitogen-activated signaling resulting in a b-TrCP2 transcriptional increase (Spiegelman et al 2002). There still remains the question of the physiological relevance of these controls modes, as unless the isoforms have different substrate specificity, opposing transcriptional regulation of the two may offset each other.…”
Section: The Ikb E3 Ubiquitin Ligasementioning
confidence: 99%
“…␤-TrCP antibody was described previously (33). Horseradish peroxidase-conjugated secondary antibodies were purchased (Cell Signaling).…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal antibody against HOS (HOS-N) was described earlier (46). Pulse-chase analysis was performed as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
“…Restricting NF-B Activation-We previously found that an overall abundance of ␤-TrCP/HOS proteins in cells is important for regulating activity of SCF ␤-TrCP/HOS E3 ubiquitin ligases and NF-B activation (41,46,53,54). The function of ␤-TrCP proteins can easily be disrupted by forced expression of viral Vpu protein, which acts as a pseudo-substrate and squelches ␤-TrCP to prevent its binding to phosphorylated I B (55,56).…”
Section: Lmp1-95-8 Is Capable Of Squelching Cellular Hos Andmentioning
confidence: 99%